Quality of life and Public Health: Interventions and perspectives (Research, Society and Development, 2022)
Over the years, the population's quality of life has been a problem discussed by public health due to the lack of health care which results in serious future losses, in addition to causing large expenditures to the State to fund more investments in health sectors by the society's lack of care in developing healthy habits on a daily basis. Thus, the present work aims to address quality of life from the perspective of public health, listing necessary interventions and perspectives. In addition, the results showed that interventions and perspectives related to quality of life require integration of health sectors with the bias of developing intervention protocols that can influence the general population to take better care of their mental and physical health, avoiding harm futures such as depression, sedentary lifestyle, chronic diseases, among other problems. Thus, the research concluded that there are still barriers to making the quality of life effective in society, due to the lack of interventions that should take place effectively in places such as schools, business organizations, neighborhoods, etc. Making public health an essential means of changing people's behavior, especially those who have problems related to physical and mental health. In this conception, quality of life and public health is considered a relevant benefit in contemporary times, being imposed as a health aspect that aims to promote improvements in healthy physical and mental well-being, achieving its goals and activating competitiveness in a harmonious way.